The Effect of Sharia Share, Sukuk, Sharia Mutual Funds and Exchange on the National Economic Growth - Yani, Devi; Kismawadi, Early Ridho; Nasution, Ismail Fahmi Ar Rauf; Bahri, M. Irvanni (Universitas Islam Negeri Sunan Kudus, 2022)
The thesis entitled